Corak Hadis dalam Kitab Sunan Imam Abu Dawud: The Characteristics of Hadith in the Sunan of Imam Abu Dawud - M. Nur Harisuddin (Fenomena, 2007)
Muslims often accept Sunan Abu Dawud without critical awareness, even though it contains not only authentic hadiths but also hasan and weak hadiths. As part of the kutub as-sittah, Sunan Abu Dawud focuses on legal hadiths (ahkam), organizing its chapters by fiqh themes. This library research, using content analysis, aims to identify the characteristics of hadiths in Sunan Abu Dawud and provide guidance on how to quote them. The main findings show that Abu Dawud himself stated that his book contains authentic hadiths, those resembling authentic (hasan li ghairihi), those close to authentic (hasan li dzatihi), and weak hadiths that he either commented on or left unremarked. Although considered a primary reference, weak hadiths in Sunan Abu Dawud may still be used to support the virtues of deeds but not as strong legal foundations. This study recommends that users of Sunan Abu Dawud be selective, avoid quoting hadiths left uncommented by Abu Dawud without deep study, and understand that the category of weak here differs from that of later scholars. Penerimaan umat Islam terhadap kitab Sunan Abu Dawud seringkali tanpa kesadaran kritis, padahal kitab ini tidak hanya memuat hadits sahih tetapi juga hadits hasan dan dhoif. Sebagai bagian dari kutub as-sittah, Sunan Abu Dawud difokuskan pada hadits-hadits ahkam (hukum), sehingga sistematikanya mengikuti bab-bab fikih. Penelitian kepustakaan dengan metode analisis isi ini bertujuan mengidentifikasi corak hadits dalam Sunan Abu Dawud serta memberikan panduan dalam pengambilannya. Temuan utama menunjukkan bahwa Abu Dawud sendiri menyatakan kitabnya berisi hadits sahih, yang menyerupai sahih (hasan li ghairihi), yang mendekati sahih (hasan li dzatihi), serta hadits dhoif yang diberi komentar atau didiamkan. Meskipun termasuk kitab rujukan utama, hadits dhoif dalam Sunan Abu Dawud masih dapat diamalkan untuk fadhailul a’mal, namun tidak untuk dasar hukum yang kuat. Penelitian ini merekomendasikan agar pengguna kitab Sunan Abu Dawud bersikap selektif, tidak mengambil hadits tanpa komentar Abu Dawud tanpa kajian mendalam, serta memahami bahwa kategori dhoif di sini berbeda dengan dhoif dalam pengertian ulama lain.